Vitamin A deficiency in the MENA region: a 30-year analysis (1990–2019) - Safiri, Saeid; Mousavi, Seyed Ehsan; Nejadghaderi, Seyed Aria; Motlagh Asghari, Kimia; Karamzad, Nahid; Sullman, Mark J. M.; Kolahi, Ali-Asghar; Abdollahi, Morteza (Frontiers in Nutrition, 2024)
Background Vitamin A deficiency (VAD) is a common micronutrient deficiency that imposes a substantial burden worldwide. This study examined the burden of VAD from 1990 to 2019 in the Middle East and North Africa (MENA) region by age, sex and sociodemographic index (SDI). Methods The data were obtained from the Global Burden of Disease (GBD) 2019 database. We reported the prevalence, incidence, and years lived with disability (YLDs) that were attributable to VAD for the MENA region, along with its constituent countries. Results In 2019, the MENA region had 30.6 million prevalent cases of VAD, with an age-standardized prevalence rate of 5249.9 per 100,000 population. In addition, VAD was responsible for 62.2 thousand YLDs, with an age-standardized YLD rate of 10.2 per 100,000. The age-standardized prevalence [50.3% (−55.9 to −44.7)] and YLD [−49.3% (−55.3 to −43.1)] rates of VAD have significantly decreased since 1990. In 2019, the MENA region’s VAD-attributable YLD rate was below the global average for males and females across all age groups. Additionally, SDI was negatively associated the age-standardized YLD rate of VAD. Conclusion This study underscores the necessity of frequently updating health data and developing guidelines and regulations to prevent, detect early, and effectively treat VAD in the MENA countries.